2014
DOI: 10.1016/j.sjpain.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

GCH1 variants, tetrahydrobiopterin and their effects on pain sensitivity

Abstract: Background A great proportion of the variation in pain experience and chronicity is caused by heritable factors. Within the last decades several candidate genes have been discovered either increasing or decreasing pain sensitivity or the risk of chronic pain in humans. One of the most studied genes is the GCH1 gene coding for the enzyme GTP cyclohydrolase 1 (GCH1). GCH1 catalyses the initial and rate-limiting step in the biosynthesis of tetrahydrobiopterin (BH4). The main function of BH4 is regulation of monoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…the nociceptive system [2]. Here, we aimed to examine the mechanism(s) behind the acute BH4-evoked nociception in mice.…”
Section: Mechanisms Of Action Of Bh4mentioning
confidence: 99%
See 3 more Smart Citations
“…the nociceptive system [2]. Here, we aimed to examine the mechanism(s) behind the acute BH4-evoked nociception in mice.…”
Section: Mechanisms Of Action Of Bh4mentioning
confidence: 99%
“…BH4 is therefore crucial for the biosynthesis of catecholamines, serotonin and nitric oxide (NO) [1,2]. Given the pleiotropic biochemical properties of BH4, it is implicated in a number of pathological conditions, such as cardiovascular diseases, neurological diseases and psychiatric disorders [1,3] pathway has also been recognised as a potential, new target for the development of novel analgesics [2,4]. This was triggered by findings that demonstrated a link between BH4 biosynthesis and pain persistence in humans and rodents [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding genetic contribution to individual differences in pain sensitivity could have substantial implications for predicting pain sensitivity and modulating pain therapy. A number of pre‐clinical studies have demonstrated that inhibition of enzymes involved in the biosynthetic pathway of BH4 produces analgesic effects in different animal models of pain . Early research revealed the potential predictive value of GCH1 genotyping in terms of clinical outcome following surgical treatment for degenerative disc disease (DDD) .…”
Section: Discussionmentioning
confidence: 99%